Thermal crack network on CVD TiCN/α-Al2O3 coated cemented carbide cutting tools. (June 2019) - Gassner, Martina; Schalk, Nina; Tkadletz, Michael; Czettl, Christoph; Mitterer, Christian
Abstract: TiCN/α-Al2 O3 coatings grown by thermally activated chemical vapor deposition (CVD) on cemented carbide cutting inserts typically exhibit a thermal crack network. Although these coated inserts are frequently industrially used for various cutting operations, there is still a lack in understanding of formation and characteristics of these cracks. Thus, the present work focuses on the investigation of the crack network observed on the surface as well as within the layers of CVD TiCN/α-Al2 O3 coated cemented carbide cutting inserts. The samples were investigated in different conditions, i.e. in the as-deposited state, after post-treatment by wet-blasting, after annealing, after wet-blasting and annealing, and after face turning, by scanning electron microscopy. Cross-sections of cracked areas were prepared by focused ion beam milling to evaluate crack formation and opening. Further, diffusion processes within the cracks were investigated by energy-dispersive X-ray spectroscopy. While wet-blasting results in closure of thermal cracks near the coating surface due to the introduction of compressive stresses, this effect is equalized after annealing and after turning; cracks are filled with TiO2 caused by oxidation of the TiCN base-layer and reaction with Al2 O3 and – in the case of turning – by workpiece material. Highlights: Characterization of the thermal crack network on CVD TiCN/Al2 O3 coated cutting inserts. Crack extension investigated by scanning electron microscopy. Crack closure influenced by post-treatment, annealing and turning. Thermal cracks partially filled with TiO2 and workpiece material components after turning.